(3GdefgL GdMfja aj eYfi GSeg JYGdi dWjas - (3GdeUQj, GdTGaYj, CHh HcQ Hf UGdM GdcJGej, J(B1051(3g`s ((3YHO GdQMef Hf GdSjO CMeO GdNWjH GdOeTbjs)
(3ChdgG (B:s
(3GdMeO ddg dWja GdUfY hUGfY GddWa Ydi GdOhGe hCaVd GdUdGI hCJe GdSdGe Ydi SjOfG eMeO GdeHYhK HGdfHhI hGdQSGdI Edi LejY GdCfGes
(3BNQgG (B:s
(3hCSCd Gddg SHMGfg hJYGdi Cf jJLGhR dj YeG JcdaJg hdSJ ef Cgdg hCf jJZeOfj HYahg hQMeJg hcQeg haVdg hCf jLeYfj aj LfJg CfG hef SJQfj hCMHfj hCMHHJg dCLdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 1 / 438s
(3gOjI GdYGQajf(B: 1 / 240s
(3EjVGM Gdecfhf(B: 2 / 591s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs